Mental health problems of second generation children and adolescents with migration background - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2017)
Objective: Despite the growing number of young second-generation immigrant (SGI) children and adolescents, studies about their mental health are rare. The objective of this study was to investigate the mental health problems of SGI children and adolescents in Istanbul, Turkey. Methods: In a clinical sample the mental health of 54 SGIs and 50 native children and adolescents were examined using the Schedule for Affective Disorders and Schizophrenia for School Aged Children-Present and Lifetime Version (K-SADS-PL) and Children's Global Assessment Scale. The assessments were carried out by a blinded rater. Results: SGI children had higher rates of psychiatric disorders such as depression (p=0.001), post-traumatic stress disorder (PTSD) (p=0.011) and anxiety disorders (p=0.013), more comorbid disorders and lower functionality scores compared to their native counterparts (p=0.001). Conclusions: SGI children seem to have higher rates of psychiatric disorders most probably due to migration-induced burdens. The professionals treating SGI children should have more awareness for these problems to be able to approach them in a culture and language sensitive way.
Keywords: Second-generation; immigrant; mental; health; psychiatric; disorders; K-SADS; children; adolescents; PARENTAL TRAUMA; IMMIGRANT; DISORDERS; CARE; GUIDANCE; IMPACT; FOCUS